Management system certification benefits: Where do we stand? - Luis Miguel Ciravegna Martins da Fonseca; José Pedro Domingues; Pilar Baylina Machado; Mario Calderón (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: The implementation and certification of Management Systems International Standards, such as ISO 9001 and ISO 14001, achieved a high international recognition, with more than 1 million organizations with their Quality Management Systems certified worldwide. Researchers have been paying considerable attention to this theme and the number of published articles has robustly grown. Although on an overall basis, the research results support the existence of positive impacts on the adoption and certification of these International Standards, there are various inconsistencies and contradictory results, leading to some controversy over its impacts for organizations. This study aims to bring a longitudinal time perspective to this area of research, analyzing the articles published since 1996, on the benefits of Management Systems Certification. A longitudinal perspective of countries of authors origin, keywords and journals is presented, complemented with an evaluation of the research results. Design/methodology/approach: A Bibliometric Study supported the research, with data collected from Web of Science, SCOPUS, and Research Gate data bases. Following the detailed analysis of the journal titles, articles abstracts and their full content, an evaluation scale was adopted to assess if the results support the existence of a positive relationship between Management System Certification and economic, financial or stakeholder results. Findings: The results evidence a steep increase in the number of publications addressing Management Systems Certification benefits, that mainly originate from Europe (48%) and East Asia and Pacific (23%), with Spain as the leading country (accounting for 14% of the total number of articles published between 1996 and April 2017). Journal of Cleaner Production (Environmental Management System Certification) and Total Quality Management and Business Excellence journal (Quality Management Systems Certification) are the leading journals for disseminating the research and the most used keywords are "Quality/Environment", "ISO 9001/14001", "Performance", "Management Systems" and "Certification". There are also insights that the research is now open to other Management Systems either than Quality and Environment. The systematic review of the selected papers shows that the Management Systems adoption and certification brings fairly positive benefits (average 2,34 in a 1 to 5 Likert type scale) for the certified organizations, although some variations are observed. Some avenues for future research should consider the reliability and validation of measures; sampling and biases errors; the identification of control, moderating and mediating variables; the consideration of time and situational contingencies; and the search for explanations for cause and effect relationships. The results of this research support the view that the investigation of Management Systems Certification benefits is indeed an issue of high academic and practitioners interest. This research, although subject to some subjective evaluation of the authors, and acknowledging that the research articles are not always comparable, aims to give some insights for this continuous research field. Research limitations/implications: Although the authors took measures to minimize subjectivity, it should be noted that the evaluation could be subject to the authors own interpretation and the research articles are not always comparable. Originality/value: This research presents a longitudinal and comprehensive evaluation of the articles published since 1996 addressing the topics of the benefits of Management System Certification. It highlights trends and gives contribution for future research, on a field of intense academic and practitioners interest.
Keywords: 650; management systems; certification; benefits; systematic review; ISO; bibliometric study